A Desain Aplikasi E-Commerce Ikan Tuna Berbasis Android - Pontoh, Fransisca Joanet (Jurnal Teknologi Informasi Indonesia (JTII), 2021)
The development of the use of mobile applications, especially for smartphone users, makes sellers of goods and services easier to market their merchandis., Tuna frozen, a place to sell tuna with a variety of choices, wants to use the e-commerce system to increase sales so that customers can order tuna without having to come to the sale place and save energy, time, and cost. The purpose of this study is to make an Android-based tuna e-commerce application for Frozen Tuna. The method used in making this application is the method of designing the Waterfall SDLC (System Development Life Cycle) system. The software used in developing this application is Eclipse, Sublime Text, XAMPP server, SQLite database, google chrome as a web browser, programming languages PHP, CSS, JS and system design using UML (Unified Modeling Language).